2017
DOI: 10.3103/s1063457617030042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the high-temperature annealing on the structure and mechanical properties of vacuum–arc coatings from Mo/(Ti + 6 wt % Si)N

Abstract: Scanning electron microscopy with energy dispersive element microanalysis, X ray structural analysis, and microindentation were used to study the effect of the deposition conditions in a reactive nitrogen atmosphere on the growth morphology, phase composition, structure, and microhardness of vac uum-arc multilayer coatings produced by the evaporation of cathodes from Mo and (Ti + 6 wt % Si) both after their deposition and after high temperature annealing. It has been established that the use of the composite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Molybdenum is an element that is widely used as an alloying element of titanium [14,15]. Some research in the field [16][17][18] has shown that a percentage of about 20% Mo can reduce the modulus of elasticity, as it is a β-stabilizing element, leading to proper mechanical properties, similar to human bone [5].…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum is an element that is widely used as an alloying element of titanium [14,15]. Some research in the field [16][17][18] has shown that a percentage of about 20% Mo can reduce the modulus of elasticity, as it is a β-stabilizing element, leading to proper mechanical properties, similar to human bone [5].…”
Section: Introductionmentioning
confidence: 99%